Nanotechnology in Dermatology - Joao Roberto Antonio; Carlos Roberto Antonio; Izabela Lidia Soares Cardeal; Julia Maria Avelino Ballavenuto; Joao Rodrigo Oliveira (Sociedade Brasileira de Dermatologia, 2014)
The scientific community and general public have been exposed to a series of achievements attributed to a new area of knowledge: Nanotechnology. Both abroad and in Brazil, funding agencies have launched programs aimed at encouraging this type of research. Indeed, for many who come into contact with this subject it will be clear the key role that chemical knowledge will play in the evolution of this subject. And even more, will see that it is a science in which the basic structure is formed by distilling different areas of inter-and multidisciplinary knowledge along the lines of new paradigms. In this article, we attempt to clarify the foundations of nanotechnology, and demonstrate their contribution to new advances in dermatology as well as medicine in general. Nanotechnology is clearly the future.